Gendered States: Women, Unemployment Insurance, and the Political Economy of the Welfare State in Canada, 1945-1997 - Porter, Ann (Studies in comparative political economy and public policy, 2003)
In the period since the Second World War there has been both a massive influx of women into the Canadian job market and substantive changes to the welfare state as early expansion gave way, by the 1970s, to a prolonged period of retrenchment and restructuring. Through a detailed historical account of the Unemployment Insurance (UI) program from 1945 to 1997, Ann Porter demonstrates how gender was central both to the construction of the post-war welfare state, as well as to its subsequent crisis and restructuring. Drawing on a wide range of sources (including archival material, UI administrative tribunal decisions, and documents from the government, labour and women's groups) she examines the implications of restructuring for women's equality, as well as how women's groups, labour and the state interacted in efforts to shape the policy agenda. Porter argues that, while the post-war welfare state model was based on a family with a single male breadwinner, the new model is one that assumes multiple family earners and encourages employability for both men and women. The result has been greater formal equality for women, but at the same time the restructuring and reduction of benefits have undermined these gains and made women's lives increasingly difficult. Using concepts from political economy, feminism, and public policy, this study will be of interest across a range of disciplines. --Publisher's description
Keywords: Economic policy; Employment; History; Social policy; Unemployment insurance; Women